2017
DOI: 10.1007/s11356-017-9356-z
|View full text |Cite
|
Sign up to set email alerts
|

The AhRR-c.565C>G transversion may increase total antioxidant capacity levels of the seminal plasma in infertile men

Abstract: The Aryl hydrocarbon receptor (AhR)-repressor (AhRR) is a regulator of the AhR pathway, which plays an important role in xenobiotic and reactive oxygen species (ROS) metabolism. Total antioxidant capacity (TAC) is a major factor in semen quality that protects sperm against ROS stress. Malondialdehyde (MDA) is the indicator of lipid peroxidation damage that is occurred due to ROSs. In this study, we determined and compared the MDA and TAC levels of infertile men's semen and blood plasma regarding genotype group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 51 publications
0
14
1
Order By: Relevance
“…Our results demonstrate that the AhRR codon Pro 185 genotype is associated with both susceptibility and severity of infertility. In addition, the present study suggested that the wild‐type allele of Pro185 is relevant to the incidence of severe infertility …”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Our results demonstrate that the AhRR codon Pro 185 genotype is associated with both susceptibility and severity of infertility. In addition, the present study suggested that the wild‐type allele of Pro185 is relevant to the incidence of severe infertility …”
Section: Discussionmentioning
confidence: 58%
“…In addition, there are environmental factors for endocrine disruptors, it can be here mentioned that endocrine disrupters are chemicals that interfere in the body's endocrine system . In addition, the environmental factors impressed the systems of genital, neurological, and human immunity of the human body and the wildlife . A wide range of materials have been recognized as endocrine disrupters including drugs, dioxins and dioxin compounds, such as polychlorinated biphenyls, dichlorodiphenyltrichloroethane, and other pestilences .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The MDA in seminal plasma can reflect the degree of peroxidative damage to spermatozoa (Agarwal et al, 2014). In general, our MDA value (1.02 nmol/ml) was slightly higher than the value of 0.94 nmol/ml (infertile) reported by (Colagar et al, 2009) but lower than many other studies (Atig et al, 2017, Josarayi et al, 2017, Collodel et al, 2015. Our seminal plasma MDA values represent all men undergone IVF treatment.…”
Section: Oxidative Stress Profile In Couplescontrasting
confidence: 45%